Super-hydrophilic antifouling paint for concrete surface

By applying ultra-hydrophilic anti-fouling coatings with modified iron doped nanotitanium dioxide and other components on the concrete surface, the problem of difficulty in preventing pollution for a long time and reducing bacterial and algae breeding in the prior art is solved, and the deep cleaning and self-cleaning effect of the concrete surface is achieved, which extends the service life of the structure and has the effect of energy saving and emission reduction.

CN119799042APending Publication Date: 2025-04-11BEIJING E-SUNNY ENVIRONMENTAL PROTECTION ENG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411975518.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent pollution and reduce bacterial algae from growing on concrete surfaces for a long time, especially in hydraulic concrete, resulting in a decrease in structural strength and a shortened service life.

Method used

A super hydrophilic anti-fouling coating is used, which contains modified iron-doped nanotitanium dioxide, lithium silicate, sodium silicate and nanosilicon dioxide. By increasing the free energy of the concrete surface, it has super hydrophilicity and achieves deep cleaning and self-cleaning effects.

Benefits of technology

This coating can effectively prevent dirt adhesion and bacterial algae from growing, improve the durability and anti-fouling ability of concrete surface, extend the service life of hydraulic concrete, and have the effect of energy saving and emission reduction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building coatings, in particular to a super-hydrophilic antifouling coating for a concrete surface. The invention discloses an iron-doped nano-titanium dioxide coating which comprises the following components in percentage by weight: 15-20% of modified iron-doped nano-titanium dioxide, 5-10% of lithium silicate, 10-20% of sodium silicate, 5-10% of nano-silicon dioxide, 0.2-2% of citrate, 1-2% of quaternary ammonium salt, 0.1-0.5% of ethylene glycol and the balance of water. According to the super-hydrophilic antifouling paint disclosed by the invention, the concrete surface has super-hydrophilicity by increasing the free energy of the concrete surface, so that water has extremely low surface tension and contact viscosity on the concrete surface, a deep cleaning effect on the concrete structure surface is realized, and the technical effects of preventing fouling, reducing bacterium and algae breeding and the like are achieved; the device is particularly suitable for the surface of hydraulic concrete, enables the surface of the hydraulic concrete to have a self-cleaning effect, can reduce the resistance of a hydraulic overflowing surface, and has the effects of energy conservation and emission reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building coatings, and in particular to a super hydrophilic antifouling coating for a concrete surface. Background Art

[0002] As a multi-phase and multi-component material, concrete has a large number of defects such as pores and microscopic cracks on its surface. These defects will allow various external pollutants to attach and erode, and provide conditions for the growth of bacteria and algae. Certain types of algae and fungi can secrete acidic substances, which can corrode the surface of concrete and cause it to deteriorate. Under long-term action, the concrete surface may peel or become loose, weakening the overall strength of the structure. The presence of bacteria and algae increases the ability of the concrete surface to absorb water, which may cause additional pressure on the concrete due to freezing and expansion of water in cold climates, thereby exacerbating cracks and damage. Therefore, if the large-scale growth of bacteria and algae is not intervened, it will greatly reduce the service life of hydraulic concrete and affect the drinking water safety, water diversion safety and operation safety of water conservancy projects.

[0003] At present, in order to prevent the growth of bacteria and algae on the surface of hydraulic concrete, a "water-repellent" coating is often formed on the surface of concrete by using organic silicon materials, referring to the papillary structure on the surface of lotus leaves. The water-repellent coating has low surface energy, which can increase the contact angle of water on the concrete surface (the contact angle is greater than 90 degrees), and make the water dripping on the concrete surface form a dew-like rolling effect, thereby preventing dirt from staying and contaminating the concrete. However, the coatings currently used are all organic components, which are not resistant to ultraviolet erosion and irradiation, and most concrete (especially hydraulic concrete) is exposed to the outdoors for a long time, and is exposed to the sun and rain, which makes the material life short, the durability is poor, and it cannot be anti-fouling for a long time. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a super hydrophilic antifouling coating for concrete surface, which makes the concrete surface super hydrophilic by increasing the surface free energy of concrete, so that water has extremely low surface tension and contact viscosity on the concrete surface, achieves deep cleaning effect on the surface of concrete structure, and achieves technical problems such as antifouling and reducing the growth of bacteria and algae; the present invention is particularly suitable for use on the surface of hydraulic concrete, so that the surface of hydraulic concrete has a self-cleaning effect, and can also increase the water flow rate of the hydraulic flow surface, which has the effect of energy saving and emission reduction.

[0006] (II) Technical solution

[0007] In a first aspect, the present invention provides a super hydrophilic antifouling coating for concrete surface, which comprises, by mass percentage, 15-20% modified iron-doped nano titanium dioxide, 5-10% lithium silicate, 10-20% sodium silicate, 5-10% nano silicon dioxide, 0.2-2% citrate, 1-2% quaternary ammonium salt, 0.1-0.5% ethylene glycol and the balance water.

[0008] According to a preferred embodiment of the present invention, the particle size of the modified iron-doped nano-titanium dioxide is ≤50 nm, wherein the percentage of iron doping is 0.5-1%.

[0009] According to a preferred embodiment of the present invention, the preparation method of the modified iron-doped nano-titanium dioxide comprises preparing iron-doped nano-titanium dioxide by a sol-gel method, and then impregnating and modifying the iron-doped nano-titanium dioxide with an alkaline solution to obtain the modified iron-doped nano-titanium dioxide; the preparation method specifically comprises:

[0010] (1) mixing tetrabutyl titanate and anhydrous ethanol to obtain a first solution; mixing anhydrous ethanol, deionized water, glacial acetic acid, and trivalent iron salt to obtain a second solution;

[0011] The second solution is uniformly added dropwise to the first solution with stirring during the addition process. After the addition is completed, the mixture is aged for 10-30 hours and placed in an oven for drying to obtain a dry gel. The dry gel is ground into powder and calcined at high temperature under aerobic conditions to obtain iron-doped nano-titanium dioxide.

[0012] (2) Soaking the iron-doped nano-titanium dioxide in an alkaline solution with a pH of 10-12, taking out the iron-doped nano-titanium dioxide, and drying it to obtain modified iron-doped nano-titanium dioxide.

[0013] According to a preferred embodiment of the present invention, the alkaline solution is sodium hydroxide or potassium hydroxide.

[0014] Preferably, the ferric salt is ferric nitrate or ferric chloride; the soaking time of the alkaline solution is 2-8 hours, and the soaking temperature is room temperature to 60°C.

[0015] According to a preferred embodiment of the present invention, in the super hydrophilic antifouling coating, the mass ratio of lithium silicate to sodium silicate is 1:2.

[0016] According to a preferred embodiment of the present invention, the super hydrophilic antifouling coating comprises, by mass percentage, 20% modified iron-doped nano titanium dioxide, 7.5% lithium silicate, 15% sodium silicate, 8% nano silicon dioxide, 1.0% citrate, 1.5% quaternary ammonium salt, 0.4% ethylene glycol and the balance water.

[0017] According to a preferred embodiment of the present invention, the citrate is sodium citrate.

[0018] According to a preferred embodiment of the present invention, the quaternary ammonium salt is at least one of benzalkonium chloride, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, stearyltrimethylammonium chloride, polyquaternary ammonium salt, hexadecylpyridinium chloride, tetradecyltrimethylammonium chloride and double-chain quaternary ammonium salt.

[0019] (III) Beneficial effects

[0020] (1) The prior art has always used hydrophobic materials to increase the hydrophobicity of the surface of hydraulic concrete, and used silicone materials / fluorocarbon resins to form a hydrophobic structure layer on the concrete surface. However, the materials used to form the hydrophobic structure (including silicone materials / fluorocarbon resins, etc.) are all organic components, and have poor durability in outdoor environments. Under the erosion of ultraviolet radiation and rainwater (hydraulic concrete may also contain acidic or alkaline compound molecules), the durability is very poor and it cannot play an anti-fouling role for a long time.

[0021] The super-hydrophilic antifouling coating for concrete surface of the present invention is significantly different from the prior art in that: the present invention adopts pure inorganic materials, greatly increases the free energy of the concrete structure surface, improves the hydrophilicity of the concrete surface, makes water have extremely low surface tension on the concrete structure surface, and extremely low contact viscosity, so that water can be completely and tightly attached to the concrete structure surface, and the interface flow state is close to laminar flow, which plays a cleaning role on the concrete structure surface, reduces the attachment of pollutants and the growth of bacteria and algae. When the super-hydrophilic antifouling coating of the present invention is used for the hydraulic flow surface, the hydraulic flow surface also has a self-cleaning effect, and can also increase the water flow rate of the hydraulic flow surface (reduce the resistance to water flow), save energy and reduce emissions, purify water quality, and solve the problem of bacteria and algae growth on the surface of the existing hydraulic concrete after running for a period of time.

[0022] (2) In order to improve the ability of the antifouling coating of the present invention to stay more firmly on the concrete surface and exert a long-term antifouling effect, the present invention performs doping and modification on titanium dioxide. On the one hand, the photocatalytic efficiency of the modified iron-doped nano-titanium dioxide is improved, so that its antibacterial and bactericidal effects can be maintained for a long time. On the other hand, the antifouling coating of the present invention simultaneously utilizes active penetrating crystalline materials such as lithium silicate, sodium silicate and nano-silicon dioxide to react and consolidate with concrete, so that the nano-titanium dioxide can be solidified on the surface of the concrete, thereby improving the coating's ability to resist water flow and rain erosion, so that the coating can stay on the concrete surface for a long time and exert its antibacterial and antifouling effects. DETAILED DESCRIPTION

[0023] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods.

[0024] The invention provides a super hydrophilic antifouling coating for concrete surface, which comprises, by mass percentage, 15-20% of modified iron-doped nano titanium dioxide, 5-10% of lithium silicate, 10-20% of sodium silicate, 5-10% of nano silicon dioxide, 0.2-2% of citrate, 1-2% of quaternary ammonium salt, 0.1-0.5% of ethylene glycol and the balance of water.

[0025] Among them, modified iron-doped nano-titanium dioxide can oxidize and kill bacteria and algae on the surface of concrete, promote the reaction of active materials such as lithium silicate, sodium silicate and nano-silicon dioxide in the coating with alkali metal ions in concrete to form crystals (CSH), provide super-hydrophilicity on the concrete surface, and increase the flow capacity and self-cleaning ability of the surface hydraulic concrete flow surface. In the present invention, modified iron-doped nano-titanium dioxide is the main component, which plays an anti-fouling and sterilization effect, and uses its photocatalysis to prevent organic matter from staying and oxidize and kill bacteria and algae.

[0026] Sodium silicate, lithium silicate and nano-silicon dioxide play a repairing and consolidating role in the present invention, which can not only repair the fine cracks and defects of the concrete surface, but also disperse and solidify the modified iron-doped nano-titanium dioxide. By utilizing the penetration and crystallization characteristics of sodium silicate, lithium silicate and nano-silicon dioxide, the microscopic defects inside and on the surface of the concrete can be solidified, filled and repaired, which can not only extend the service life of the hydraulic concrete flow surface, but also reduce the adhesion probability of bacteria and algae by reducing fine cracks and defects. Sodium silicate, lithium silicate and nano-silicon dioxide can also react with alkali metal ions in concrete to form crystals (CSH), so modified iron-doped nano-titanium dioxide can be solidified on the surface of concrete, improve the ability of modified iron-doped nano-titanium dioxide to resist water flow and rain scouring, extend the residence time of modified iron-doped nano-titanium dioxide on the concrete surface, and make it play the role of anti-fouling and sterilizing algae for a long time. Nano-silicon dioxide fills the microscopic cracks on the surface of concrete and disperses and solidifies modified iron-doped nano-titanium dioxide.

[0027] Citrate plays the role of a regulator in the present invention, and is used to regulate the reaction rate of the concrete surface layer such as sodium silicate, lithium silicate, and nano-silicon dioxide. Citrate is a multidentate ligand that can be combined with iron ions in modified iron-doped nano-titanium dioxide or other metal ions that may exist (such as metal ions in lithium silicate and sodium silicate). This complexation can slow down the speed at which these metal ions participate in chemical reactions, thereby controlling the reaction rate of the entire system. Citrate also has a certain buffering capacity, which can help maintain the pH value of the solution stable and reduce the rate of change of the pH of the solution (the chemical reaction of the antifouling coating is very sensitive to the pH value). In the presence of lithium silicate and sodium silicate, citrate can reduce the potential adverse reactions between these components and prevent the generation of undesirable precipitation or gel, thereby controlling the reaction rate. Citrate can also help improve the dispersibility of each component in the coating, especially for nano-scale materials such as nano-titanium dioxide and nano-silicon dioxide. Good dispersibility improves the performance of the coating and can also avoid the problem of excessively severe local reactions caused by particle aggregation.

[0028] Quaternary ammonium salt plays the role of stabilizer in the present invention, and is used to stabilize the various components in the antifouling coating. The principle that the quaternary ammonium salt cation acts as a stabilizer is that the quaternary ammonium salt provides cations, which can exchange ions with monovalent cations on the surface of silicate anions of different polymerization degrees or monovalent cations on the surface of silicate sol to replace monovalent cations, and are surrounded by silicate anions through charge attraction adsorption, and the protective effect of steric hindrance is utilized to prevent the silicate anions from reacting with polyvalent metal ions or self-polymerization, thereby improving the stability of the antifouling coating. The quaternary ammonium salt is at least one of benzalkonium chloride, dodecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide, dioctadecyl dimethyl ammonium chloride, stearyl trimethyl ammonium chloride, polyquaternium salt, hexadecyl pyridinium chloride, tetradecyl trimethyl ammonium chloride and double-chain quaternary ammonium salt.

[0029] Ethylene glycol plays the role of a sealant in the present invention, and can provide a good reaction environment for antifouling coating on the surface of concrete. Ethylene glycol can react with alkali metal to form alkoxide, which, as a precursor in the sol-gel process, forms gel by hydrolysis and polycondensation. For example, in the presence of lithium silicate and sodium silicate, these metal ions such as lithium or sodium can react with the hydrolyzed alkoxide to form a more stable siloxane network. Therefore, ethylene glycol interacts with components such as lithium silicate and sodium silicate to help build a strong and durable protective layer, thereby enhancing the antifouling and other properties of the coating. In addition, ethylene glycol is a common antifreeze component that can lower the freezing point of water, prevent the water in the coating from freezing under low temperature conditions, and is conducive to construction in winter or cold areas.

[0030] In the present invention, the preparation method of the modified iron-doped nano-titanium dioxide comprises preparing the iron-doped nano-titanium dioxide by a sol-gel method, and then impregnating and modifying the iron-doped nano-titanium dioxide with an alkaline solution to prepare the modified iron-doped nano-titanium dioxide; the preparation method specifically comprises:

[0031] (1) mixing tetrabutyl titanate with anhydrous ethanol to obtain a first solution; mixing anhydrous ethanol, deionized water, glacial acetic acid, and trivalent iron salt (such as ferric nitrate or ferric chloride) to obtain a second solution; uniformly dropping the second solution into the first solution, stirring during the dropping process, aging for 10-30 hours, and drying in an oven to obtain a dry gel, grinding the dry gel into powder, and calcining at high temperature under aerobic conditions to obtain iron-doped nano-titanium dioxide;

[0032] (2) Soaking the iron-doped nano-titanium dioxide in a strong alkaline solution such as sodium hydroxide or potassium hydroxide with a pH of 10-12, taking out the iron-doped nano-titanium dioxide, and drying it to obtain modified iron-doped nano-titanium dioxide. The soaking time is 2-8 hours, and the soaking temperature is room temperature to 60°C.

[0033] The percentage of iron doping in the modified iron-doped nano-titanium dioxide is 0.5-1% by controlling the dosage of iron salt and tetrabutyl titanate. The particle size of the prepared modified iron-doped nano-titanium dioxide is ≤50nm by controlling the speed of dripping the second solution into the first solution, the aging time and the grinding degree.

[0034] The present invention has the following technical effects compared with pure nano titanium dioxide (TiO2) by iron-doped nano titanium dioxide (Fe-TiO2): ① Enhanced photocatalytic activity: The doping of iron ions can effectively expand the light absorption range of TiO2, making it not only effective under ultraviolet light, but also responsive to visible light. This greatly improves its photocatalytic efficiency, especially under natural light conditions. ② Improved separation of electron-hole pairs: A major disadvantage of TiO2 is that the electrons and holes generated under light are easy to recombine, thereby reducing the photocatalytic efficiency. The doping of iron ions can serve as a capture center, prolong the carrier life, reduce the recombination rate, and thus improve the utilization efficiency of photogenerated charges. ③ Improved antibacterial algae performance: Due to its improved photocatalytic activity, Fe-TiO2 can more effectively generate active oxygen species (such as superoxide, hydroxyl radicals, etc.), which have a destructive effect on the cell wall of microorganisms, thereby enhancing the antibacterial performance of the material. ④ Increased stability: An appropriate amount of iron doping can improve the chemical stability and thermal stability of TiO2, so that the material can still maintain good performance under long-term use or high temperature environment. In addition, iron doping can also fine-tune the band gap width of Fe-TiO2, further optimizing its optical and electrical properties. Nano-titanium dioxide prepared using tetrabutyl titanate (TBT) as a precursor is anatase.

[0035] The second solution is slowly and evenly dripped into the first solution, resulting in the hydrolysis and polycondensation of tetrabutyl titanate to form a precursor of titanium dioxide, and the iron ions are evenly dispersed therein to achieve the doping of the iron element. The dried gel is ground into a powder and then calcined at high temperature under aerobic conditions. The calcination process can not only remove organic components, but also promote the formation of nanoparticles, while ensuring that the iron element is successfully doped into the titanium dioxide lattice. Alkaline solution modification can change the chemical properties of the surface of nanomaterials, increase hydrophilicity and charge density, increase the number of hydroxyl groups (-OH) on the surface of nano-titanium dioxide, and may also cause the loss of oxygen atoms in the lattice to form oxygen vacancies. These oxygen vacancies act as electron traps, which can change the electrical properties of the material and improve the photocatalytic activity. Alkali treatment may cause some iron ions or titanium ions to escape or rearrange from the surface of the nanoparticles, resulting in local lattice distortion. This structural imperfection can enhance the optical absorption performance of the material. In short, after alkali solution immersion treatment, the hydrophilicity and photocatalytic performance of the material are mainly improved.

[0036] In the super-hydrophilic antifouling coating, the mass ratio of lithium silicate to sodium silicate is 1:2. Sodium silicate and lithium silicate can be used in combination to improve the sealing and durability of the coating on the surface of concrete. Lithium silicate can react with free calcium hydroxide in concrete to generate more hydrated calcium silicate gel (CSH), thereby filling the pores and enhancing the strength of concrete. The formed CSH gel can effectively reduce the porosity inside the concrete, improve its impermeability, and prevent the invasion of moisture and other harmful substances. After drying, the sodium silicate solution will quickly form a hard protective film, which helps to quickly close the pores on the surface of the concrete and provide an immediate protective effect; sodium silicate is cheap and easy to obtain, and is suitable for large-scale construction. Sodium silicate can quickly form a preliminary protective layer, while lithium silicate continues to react to further strengthen the protective layer; it can achieve a good sealing effect in a short time, while maintaining good impermeability, wear resistance and durability for a long time. The combination of lithium silicate and sodium silicate can help ensure uniform distribution of the coating and increase the adhesion between the coating and the substrate, thereby supporting ingredients such as modified iron-doped nano-titanium dioxide to exert their superhydrophilic and self-cleaning functions.

[0037] The super-hydrophilic antifouling coating of the present invention is applied to the surface of concrete, especially the surface of the flow surface of hydraulic concrete, and can play a good role in anti-pollution and anti-bacterial algae. After the antifouling coating is cured, water can completely and tightly adhere to the surface of the concrete structure to achieve a cleaning effect on the surface of the concrete. Water can completely spread and tightly fit the surface of the concrete, penetrate into the small pores and cracks on the surface, thereby helping to remove embedded dirt or pollutants. The present invention uses sodium silicate, lithium silicate and nano-silicon dioxide to fill, repair and consolidate the shallow cracks of concrete, reduce the probability of bacteria and algae staying, prevent external pollutants from penetrating into the concrete structure to destroy the concrete structure, and consolidate the modified iron-doped nano-titanium dioxide for a long time on the surface of the concrete structure to play the ability of photocatalytic sterilization of algae. The super-hydrophilic antifouling coating of the present invention has extremely strong resistance to ultraviolet radiation and acid and alkali compared to resin coatings such as silicone. In particular, when used for the flow surface of hydraulic concrete, it has a strong ability to resist water flow and rain scouring, keeps the hydraulic flow surface clean, and reduces the number of flushing and maintenance frequency of the flow surface. In addition, the present invention is also applicable to concrete structure surfaces that are in contact with water for a long time, such as dams or reservoir slopes constructed of concrete.

[0038] The invention scheme is further described below in conjunction with the preferred embodiments of the present invention.

[0039] Example 1

[0040] The present embodiment provides a super hydrophilic antifouling coating, which comprises, by mass percentage, 20% modified iron-doped nano titanium dioxide, 7.5% lithium silicate, 15% sodium silicate, 8% nano silicon dioxide, 1.0% sodium citrate, 1.5% dodecyltrimethylammonium chloride, 0.4% ethylene glycol and the balance water.

[0041] The preparation method of modified iron-doped nano-titanium dioxide includes preparing iron-doped nano-titanium dioxide by sol-gel method (refer to the prior art), and then modifying the iron-doped nano-titanium dioxide by alkaline solution. The specific preparation method is as follows:

[0042] (1) Slowly drip n-butyl titanate into anhydrous ethanol and mix well to obtain a first solution; add ferric nitrate, glacial acetic acid and ethanol into water to obtain a second solution; slowly drip the second solution into the premixed first solution, and after the dripping is completed, continue stirring for 40 minutes to obtain a sol; let it stand for 24 hours, then place it in a vacuum box at 55°C for drying, grind it after drying, and then place it in a muffle furnace for aerobic roasting, and grind it again after roasting to obtain iron-doped nano titanium dioxide.

[0043] (2) Soaking the iron-doped nano-titanium dioxide in a sodium hydroxide solution having a pH of 11.5 at room temperature for 5 hours, taking out the iron-doped nano-titanium dioxide, and drying the solution to obtain modified iron-doped nano-titanium dioxide. The particle size of the modified iron-doped nano-titanium dioxide is ≤50 nm, and the iron doping content is 1 wt%.

[0044] Example 2

[0045] This embodiment provides a super-hydrophilic antifouling coating, which includes, by mass percentage, 15% modified iron-doped nano-titanium dioxide, 10% lithium silicate, 20% sodium silicate, 5% nano-silicon dioxide, 2.0% sodium citrate, 2.0% hexadecyltrimethylammonium bromide, 0.3% ethylene glycol, and the balance of water. The preparation method of the modified iron-doped nano-titanium dioxide is the same as that of Example 1, wherein the iron doping content is 0.75wt%.

[0046] Example 3

[0047] This embodiment provides a super hydrophilic antifouling coating, which includes, by mass percentage, 18% modified iron-doped nano titanium dioxide, 8% lithium silicate, 15% sodium silicate, 7% nano silicon dioxide, 1.2% sodium citrate, 1.6% dioctadecyl dimethyl ammonium chloride, 0.5% ethylene glycol and the balance water. The preparation method of the modified iron-doped nano titanium dioxide is the same as that of Example 1, wherein the iron doping content is 0.56wt%.

[0048] Comparative Example 1

[0049] In this comparative example, the "modified iron-doped nano-titanium dioxide" in Example 1 is replaced with an equal amount of "iron-doped nano-titanium dioxide", and the iron-doped nano-titanium dioxide is not modified by soaking in alkali solution. The remaining composition of the super-hydrophilic antifouling coating of this comparative example is the same as that of Example 1.

[0050] Comparative Example 2

[0051] In this comparative example, the sodium silicate and lithium silicate in Example 1 are removed, and the content of nano silicon dioxide is adjusted to 30%; the remaining composition of the super hydrophilic antifouling coating of this comparative example and the modified iron-doped nano titanium dioxide are the same as those in Example 1.

[0052] Performance Testing

[0053] The coatings prepared in the above examples were applied on a 20cm×10cm×2cm concrete test block, and a waterproof adhesive strip was bonded to both sides of the length direction of the concrete test block to form a water channel structure. The method for applying the super hydrophilic antifouling coating is as follows: first clean the surface of the concrete test block to remove grease and stains, and then directly apply the coating when the base surface is saturated with water but without visible water, with a coating amount of 0.35Kg / m 2 After laying flat to dry in the shade, measure the antibacterial and algae ability as follows.

[0054] (1) Selecting algae from water samples

[0055] Using the upright microscope method: 1L of water sample is fixed in a container with Lugo's reagent. After natural sedimentation for 24 hours, the supernatant is sucked out by siphoning and concentrated to 30-50mL. Then 1mL is put into a blood cell counting plate and counted under an upright microscope. The algae with the largest number are selected as the target algae. After the test, it was decided to culture Chlorella as the target algae.

[0056] (2) Cultivation of selected algae

[0057] The algae were inoculated in BG-11 culture medium in a triangular flask at an OD value of 0.05 at 730 nm, with gentle shaking at a speed of 70 rpm, a 4100K fluorescent tube as the light source, a light intensity of 2000 lux, a photoperiod of 10L:14D, and a culture temperature of 25±1°C. The experimental algae were cultured to the logarithmic growth phase, centrifuged at 4000 rpm, and resuspended in 1 / 3 BG-11 culture medium to a cell density of 10 6 / ml for later use.

[0058] (3) Test method

[0059] Take the original concrete test block (control) and the test block (test product) coated with super-hydrophilic antifouling coating, place the side coated with super-hydrophilic antifouling coating upwards, and place it on one side of the test box with a pad to form a slope of about 30 degrees. Use a circulating pump to pump the algae solution cultured in step (2) into a high-position water storage tank. Five holes are opened at the bottom of the water storage tank, each of which is connected to a hose. The lower end of the hose is opened and placed on the top of the concrete test block. The water flows from the top of the concrete test block to the test box, and then is transported to the water storage tank through the circulation pipeline. This cycle is repeated for 12 days. The test period is in late August, with an average daily temperature of 30.4℃ and about 9 hours of sunshine per day.

[0060] (4) Observe the growth of bacteria and algae

[0061] The growth of algae on the surface of the test block was measured every other day and recorded by scanning with a chlorophyll fluorescence imager. The chlorophyll fluorescence value of the concrete test block was measured within the emission wavelength range of 695nm to 770nm. The relative value of Chlorella chlorophyll fluorescence was measured, and the black spots (mold) were observed with the naked eye. The measurement range was limited to the immersion line from the top to the bottom of the test block.

[0062] The results are shown in Table 1.

[0063] Table 1: Algae and fungi on the surface of each concrete test block

[0064] Group Chlorophyll fluorescence relative value of Chlorella vulgaris Dark spots Example 1 322 none Example 2 353 none Example 3 347 none Comparative Example 1 428 none Comparative Example 2 536 Dark spots appear

[0065] From the above test results, it can be seen that the super hydrophilic antifouling coating prepared by the present invention has an excellent anti-pollution effect when used on the surface of a concrete structure. The photocatalytic efficiency of the iron-doped nano-titanium dioxide used in Comparative Example 1 is low, resulting in the weakening of the antibacterial and algaecidal properties of the super hydrophilic antifouling coating under the same external conditions; the antifouling coating prepared in Comparative Example 2 cannot well consolidate and retain the modified iron-doped nano-titanium dioxide on the surface of the concrete structure for a long time. After 12 days at an ambient temperature of 30°C, it was found through a water flow test that a small amount of Chlorella and mold had grown on the surface of the concrete test block.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. These modifications or replacements, or the technical features in the above embodiments may be combined in the manner described in the embodiments if they do not conflict with each other, and these modifications, replacements or combinations do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A super hydrophilic antifouling coating for concrete surface, characterized in that: Calculated by mass percentage, it comprises: 15-20% of modified iron-doped nano titanium dioxide, 5-10% of lithium silicate, 10-20% of sodium silicate, 5-10% of nano silicon dioxide, 0.2-2% of citrate, 1-2% of quaternary ammonium salt, 0.1-0.5% of ethylene glycol and the balance of water.

2. The super hydrophilic antifouling coating according to claim 1, characterized in that: The particle size of the modified iron-doped nano titanium dioxide is ≤50nm, wherein the percentage of iron doping is 0.5-1%.

3. The super hydrophilic antifouling coating according to claim 1, characterized in that: The preparation method of the modified iron-doped nano-titanium dioxide comprises preparing the iron-doped nano-titanium dioxide by a sol-gel method, and then impregnating and modifying the iron-doped nano-titanium dioxide with an alkaline solution to prepare the modified iron-doped nano-titanium dioxide; The preparation method specifically comprises: (1) mixing tetrabutyl titanate and anhydrous ethanol to obtain a first solution; Mixing anhydrous ethanol, deionized water, glacial acetic acid, and trivalent iron salt to obtain a second solution; The second solution is uniformly added dropwise to the first solution with stirring during the addition process. After the addition is completed, the mixture is aged for 10-30 hours and placed in an oven for drying to obtain a dry gel. The dry gel is ground into powder and calcined at high temperature under aerobic conditions to obtain iron-doped nano-titanium dioxide. (2) Soaking the iron-doped nano-titanium dioxide in an alkaline solution with a pH of 10-12, taking out the iron-doped nano-titanium dioxide, and drying it to obtain modified iron-doped nano-titanium dioxide.

4. The super hydrophilic antifouling coating according to claim 3, characterized in that: The alkaline solution in step (2) is sodium hydroxide or potassium hydroxide.

5. The super hydrophilic antifouling coating according to claim 3, characterized in that: In step (1), the trivalent iron salt is ferric nitrate or ferric chloride; in step (2), the soaking time of the alkaline solution is 2-8 hours, and the soaking temperature is room temperature to 60°C.

6. The super hydrophilic antifouling coating according to claim 1, characterized in that: The mass ratio of lithium silicate to sodium silicate is 1:

2.

7. The super hydrophilic antifouling coating according to claim 1, characterized in that: The super-hydrophilic antifouling coating comprises, by mass percentage, 20% of modified iron-doped nano titanium dioxide, 7.5% of lithium silicate, 15% of sodium silicate, 8% of nano silicon dioxide, 1.0% of citrate, 1.5% of quaternary ammonium salt, 0.4% of ethylene glycol and the balance of water.

8. The super hydrophilic antifouling coating according to claim 1, characterized in that: The citrate is sodium citrate.

9. The super hydrophilic antifouling coating according to claim 1, characterized in that: The quaternary ammonium salt is at least one of benzalkonium chloride, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, stearyltrimethylammonium chloride, polyquaternary ammonium salt, hexadecylpyridinium chloride, tetradecyltrimethylammonium chloride and double-chain quaternary ammonium salt.

Citation Information

Cited By

  • Preparation process of PET (Polyethylene Terephthalate) film laser printing coating

    CN120173462A